LNF Micro-Contact using MEMS and EFF Technology - Bhuiyan, Moinul; Takemasa, Eiichiro; Bhuiyan, Munira (2013)
Enable the design of a small contact spring for applications requiring high density, high speed and high durability. A low normal force (LNF) contact spring with high performance is fabricated using a unique combined MEMS photo resist lithography and electro fine forming (EFF) technology. Reducing a total contact material cost of a connector, a high-Hertz stress with LNF contact will be a key technology in the future. Only radius r5m tip with 0.1N force contact provides an excellent electrical performance which is much sharper than conventional contact. 0.30million cycles durability test was passed at 300m displacement and the contact resistance was ≦50mΩ.